Relationship between work environment and organizational commitment among private school teachers in Klang Valley - Ng, Pek Cheng; Abdul Kadir, Suhaida (Human Resource Management Academic Research Society, 2018)
The main purpose of this study is to determine the relationship between work environment and organizational commitment among private school teachers in Klang Valley. Survey questionnaires were distributed to five private schools. 110 private school teachers participated in the survey. Data regarding organizational commitment and work environment were analyzed by using IBM SPSS Software version 22.0. Descriptive statistic was employed to identify level of teachers' work environment and organizational commitment. Pearson correlation was used to analyze the relationship between work environment and organizational commitment among private school teachers. T-test is to identify the difference of private school teachers’ organizational commitment based on gender. The results demonstrated that there are moderate relationships between teachers' work environment and teacher's organizational commitment. The findings also revealed that there are no significant different between female and male private school teachers in organizational commitment.